Experimental Acute Pancreatitis Models: History, Current Status, and Role in Translational Research - Yang, Xinmin; Yao, Linbo; Fu, Xianghui; Mukherjee, Rajarshi; Xia, Qing; Jakubowska, Monika A.; Ferdek, Pawel E.; Huang, Wei (Frontiers in Physiology, 2020)
Acute pancreatitis is a potentially severe inflammatory disease that may be associated with a substantial morbidity and mortality. Currently there is no specific treatment for the disease, which indicates an ongoing demand for research into its pathogenesis and development of new therapeutic strategies. Due to the unpredictable course of acute pancreatitis and relatively concealed anatomical site in the retro-peritoneum, research on the human pancreas remains challenging. As a result, for over the last one hundred years studies on the pathogenesis of this disease have heavily relied on animal models. This review aims to summarise different animal models of acute pancreatitis from the past to present and discuss their main characteristics and applications. It identifies key studies that have enhanced our current understanding of the pathogenesis of acute pancreatitis and highlights the instrumental role of animal models in translational research for developing novel therapies.